2017 IEEE International Symposium on Medical Measurements and Applications (MeMeA) 2017
DOI: 10.1109/memea.2017.7985857
|View full text |Cite
|
Sign up to set email alerts
|

High performance, low cost carbon nanotube yarn based 3D printed electrodes compatible with a conventional screen printed electrode system

Abstract: 3D printing technology has been widely used as a rapid prototyping fabrication tool in several fields, including electrochemistry. In this work, we incorporate 3D printing technology with carbon nanotube yarns for electrochemical sensing of dopamine in the presence of ascorbic acid and uric acid. The novel 3D printed electrode provides a circular concavity detection zone with grooves to insert three electrodes. The electrode connections are fully compatible with conventional screen printed electrode workstatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Furthermore, alternative electrode fabrication technology involving 3D printing has been used with CNT yarns to develop a new platform for electrochemical sensing of dopamine in the presence of UA and AA [31]. This innovative CNT yarn 3D printed electrode displayed promising electrocatalytic activity for the redox reaction of DA in the presence of AA and UA.…”
Section: Neurosensing Via Cyclic Voltammetrymentioning
confidence: 99%
“…Furthermore, alternative electrode fabrication technology involving 3D printing has been used with CNT yarns to develop a new platform for electrochemical sensing of dopamine in the presence of UA and AA [31]. This innovative CNT yarn 3D printed electrode displayed promising electrocatalytic activity for the redox reaction of DA in the presence of AA and UA.…”
Section: Neurosensing Via Cyclic Voltammetrymentioning
confidence: 99%
“…Thus, the temporal resolution is higher than CFMEs. 18,21,22 In addition, the secondary oxidation peak, due to cyclization of the reduced species, is enhanced at CNTYMEs. 21 These peaks are not typically observed at CFMEs, because they would diffuse away from the surface, but in a structure that promotes trapping, they are easily detected.…”
mentioning
confidence: 99%
“…15 They have improved sensitivity and electron transfer kinetics for neurotransmitter detection. [16][17][18][19][20] Our previous study demonstrated that CNTYMEs trap compounds in the crevices of CNT forests, leading to thin layer cell-like electrochemical behavior. 15,16,21 Unlike CFMEs, which experience a dramatic signal loss at high repetition frequencies in FSCV, the trapping effect of CNTYMEs result in high signals for catecholamine neurotransmitters at high repetition frequencies.…”
mentioning
confidence: 99%